An Effectiveness of Nurse’s Knowledge and Practices Program Toward Care of Patient Undergoing Cardiopulmonary Bypass - Sabri, khalid Mahmood; Hassan, Hakemia Shakir Hassan (Iraqi National Journal of Nursing Specialties, 2023)
AbstractObjective : the aim of the study is to evaluate the effectiveness of nurse’s practices and knowledge program toward care of patient with cardiopulmonary bypass .Methodology: A pre-experimental design (one group pretest- posttest design) was used to carry out this study in three governmental hospitals in Baghdad ( Iraqi Centre for Heart Diseases , Ibn – Albitar Centre for Cardiac Surgery and Ibn – Alnafees Centre for Cardiothoracic and Vascular Surgery ) for the period from 15th of May 2022 into 20th of April 2023.The construction and development of the program and instruments had carry out by the researcher to measured the purposes of the study , twenty two nurses was purposively assigned for the study group . The study instrument consisted from three parts ,socio – demographic data that consist from ( 4 ) items , knowledge part that consist from ( 25 ) items , and observational checklist for practices part that consist from ( 26 ) items . Descriptive and inferential statistics was used to analyse the study data .Results : The results of the study presented that effect of nurses practices and knowledge program toward care of patient with cardiopulmonary bypass was positive with highly significant level between pretest and posttest for knowledge and practices. Conclusion :Nursing care for the patient with cardiopulmonary bypass have been improved related to the enhancement of nursing staff knowledge and practices toward cardiopulmonary bypass.Recommendations : The study recommended to apply this program as apart of continues education in hospital that perform cardiac surgery in Iraq , also encourage the ministry of health to provide educational programs that depending on standards guidelines and advanced research on cardiopulmonary bypass .